The Prime Role of Preventive Approach of Ayurveda in Autoimmune Disorder with Special Reference to Vitiligo - Smita S Kamde1 , Gaurav Sawarkar2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Vitiligo is a skin disease with unknown etiology and has unpredictability on the extent and rate of spread. Itis considered an autoimmune disorder that destroys melanocytes in the skin characterized by depigmentationor hypopigmented patches. Vitiligo patients feel distressed and suffer social stigma as it has a significantimpact on the quality of life of patients. Treatment available in contemporary medicine has its limitationsand side–effects. Hence, maintenance of health and prevention of disease is of utmost importance. Ayurvedahas incorporated this condition into broad terms of Shwitra, which is described under the heading of Kushta.Ayurveda states the causes of Shwitra may be Chhardivegadharan, Atisewan of Amla–Katu-Ushna–LavanAaharsewana, Virrudha Ahar and Atimatra Bhojan along with Navanna Sewana and Dadhi Sewana. Hence,a multidisciplinary approach is needed to treat such conditions with lifestyle medications and dietaryinterventions. Ayurveda has a holistic and scientific method in health management. It emphasizes muchmore on diet and regimen, along with medicines. Ayurveda deals with Pathya –Vyavastha in a very scientificway. Here an attempt has been made to compile the knowledge of ancient holistic science to throw lightupon the concept of Ayurveda regarding the modification of lifestyle and the preventive measures effectiveconcerning Vitiligo which will be a subject of benefit to humankind along with the awareness of the factthat the judicious use of food and healthy lifestyle interventions are the real medicines for health, so earlyresponses are necessary for better results.